SISTEM TEKNOLOGI PEMBUATAN GULA AREN DI KAMPUNG KUTA, KECAMATAN TAMBAKSARI, KABUPATEN CIAMIS - Masduki, Aam; Alamsyah P, Suwardi; Harsono, T. Dibyo; Herlinawati, Lina (ppjbsip, 2023)
Abstract: The society of Kuta village has been preserving their local wisdom because their elders as well as their social order refer to customary rules that have been run for generations, either in preserving natural resources or cultivating lands. One of their local wisdoms is traditional systaem of technology to cultivate and to process palm trees. To the Kuta societypalm trees (aren, Arengata pinnata) are important part of their livesand they utilize almost every parts of the tree from the roots up to the fruiteither for daily life or ceremonyThey make palm sugar for offerings in ceremoniesand it is considered as energizer in daily lifeThe process of making palm sugar contains traditional knowledge of food preservation, tools maintenance and the philosophy of palm itselfThis research conducted by descriptive-analytic approach.